Alumina-Mediated π-Activation of Alkynes - Akhmetov, Vladimir; Feofanov, Mikhail; Sharapa, Dmitry; Amsharov, Konstantin (Journal of the American Chemical Society, 2021)
The ability to induce powerful atom-economic transformation of alkynes is the key feature of carbophilic π-Lewis acids such as gold- and platinum-based catalysts. The unique catalytic activity of these compounds in electrophilic activations of alkynes is explained through relativistic effects, enabling efficient orbital overlapping with π-systems. For this reason, it is believed that noble metals are indispensable components in the catalysis of such reactions. In this study, we report that thermally activated γ-Al2O3 activates enynes, diynes, and arene-ynes in a manner enabling reactions that were typically assigned to the softest π-Lewis acids, while some were known to be triggered exclusively by gold catalysts. We demonstrate the scope of these transformations and suggest a qualitative explanation of this phenomenon based on the Dewar-Chatt-Duncanson model confirmed by density functional theory calculations.
CRIS-Team Scopus Importer:2021-10-08